Do evidence‐based guidelines change clinical practice patterns?. Issue 4 (14th December 2016) - Kessel, Line; Erngaard, Ditte; Flesner, Per; Andresen, Jens; Hjortdal, Jesper
Abstract: In 2013, the Danish Health and Medicines Authorities published a National Clinical Guideline on the treatment of age‐related cataracts. The guideline provided evidence‐based recommendations on the indication for cataract surgery, cataract surgery in patients with age‐related macular degeneration, on the use of toric intraocular lenses (IOLs) to correct preoperative corneal astigmatism, the use of intracameral and topical antibiotics to prevent endophthalmitis, choice of anti‐inflammatory medication to control postoperative inflammation and prevent cystoid macular oedema, the use of immediate sequential bilateral cataract surgery and on the postoperative check‐up of patients. A questionnaire was sent to all members of the Danish Ophthalmological Society before and after publication of the guideline. The responses showed that the guideline had changed practice patterns so that surgeons were more likely to prescribe non‐steroidal anti‐inflammatory eye drops and to not prescribe topical antibiotic eye drops after the guideline was published. Other parameters, most notably the use of toric IOLs and use of postoperative examinations were more guided by reimbursement standards than by evidence‐based medicine. Thus, evidence‐based guidelines do change practice patterns unless they are counteracted by the reimbursement system.